Synthesis, crystal structure, DNA binding, cleavage and cytotxicity, antimicrobial activity of new copper(II) complex with L-ornithine and 1, 10-phenanthroline. Issue 2 (1st February 2017) - Baskaran, S.; Murali Krishnan, M.; Arumugham, M. N.
ABSTRACT: A new copper(II) complex, [Cu(phen)(L-orn)(NO3 )](NO3 ).2(H2 O) (phen = 1, 10-phenanthroline, L-orn = L-ornithine), has been synthesized and structurally characterized by elemental analyses, IR, UV-visible and single-crystal XRD techniques. The complex crystallized in a monoclinic system with space group P21, a = 10.561(5) Å, b = 6.927(5) Å, c = 15.510(5) Å, α = 90.000(5)°, β = 106.827(5)°, and γ = 90.000(5)°. The complex shows a distorted square-pyramidal (4+1) CuN3 O2 coordination sphere. The binding interaction of the present complex with calf-thymus DNA (CT-DNA) was investigated and proposed partial intercalation binding mode by UV-Vis, fluorescence, cyclic voltammetry, and viscometric techniques. The efficient cleavage activity of the complex on plasmid DNA by complex was observed from gel electrophoresis technique. The complex exhibited potent cytotoxic effects against human cell line (HepG2) and it was found to have good antibacterial and antifungal activities.